Respostas institucionais para o abastecimento público no desastre do Rio Doce: o caso de Colatina/ES - Rebuli, Karlla Cristina Gaiba (2023)
The multiple impacts arising from the Samarco S/A dam disaster in November 2015, including the interruption of water collection from the Doce River for public supply and other uses, is the subject of this research. Considering that such impacts resulted in a serious problem for the water management bodies in most of the affected municipalities, we chose the municipality of Colatina-ES among them, as an empirical reference to study how managers dealt with the problems created to respond to water demands. in this context of a sudden crisis. To this end, we mobilize as theoretical lenses the contributions of Constructivist Institutionalism (HAY, 2006; BOIN 't HART, 2003) combined with those coming from the theory of Public Action (LASCOUMES, LE GALES, 2007, HALPERN, LASCOUMES, LE GALES, 2021) with the aim of understanding: a) how the Water Policy Instruments were (if they were) mobilized to respond to the critical situation of the disaster and b) how the interpretation of institutional actors in the face of the sudden crisis influenced their actions. Methodologically, the theme was approached as a case study, through exploratory research, using qualitative methods for document analysis and empirical data collected through the application of semi-structured questionnaires to the group of managers who acted at the critical moment. As a result, it was evidenced that the ideas about the sudden crisis, that is, the interpretation of the disaster, guided the institutional actors to seek in instruments means to base their actions or, in certain cases, inactions. Ideational contestations were present in the intersubjective ideation processes, especially in the decisions about who should act and about the return of the Doce river capture. Finally, the actions undertaken in the municipality of Colatina/ES to mitigate the impacts during the period of suspension of water collection from the Doce river revolved primarily around the construction of alternative solutions to supply the population, the focus of responses revolved around public supply, which left other demands for use unattended, especially in rural areas, causing serious damage especially for small rural producers.